Climate smart agriculture and entrepreneurship with young farmers project in Zambia - Bappa Se, Marc Ghislain (Technical Centre for Agricultural and Rural Cooperation, 2018)
Marc Ghislain Bappa Se, shares some outcomes of the Climate Smart Agriculture and Entrepreneurship in Young Farmers Clubs Project, supported by CTA in Zambia.